Genetic polymorphism (rs6587666) in FLG protects from eczema in admixed Brazilian children population with high African ancestry. Issue 2 (February 2023) - Rios, Raimon; Magalhães da Silva, Thiago; Strina, Agostino; Forno, Erick; Costa, Ryan; Celedón, Juan C.; Barreto, Maurício L.; Figueiredo, Camila Alexandrina
Abstract: Genetic variants in filaggrin ( FLG ) are key in eczema and are less common in Africans than in Europeans and Asians. Here we examined the association between FLG Single Nucleotide Polymorphisms (SNPs) and eczema in a population of admixed Brazilian children and whether African ancestry modifies this association. We included 1010 controls and 137 cases and ran logistic regressions between SNPs in FLG and eczema in the studied population and also stratified the analyses according to the degree of African ancestry. In addition, we tested the replication of the findings on an independent set of individuals, as well as, we verified the impact on FLG expression according to each SNP genotype. The T allele of SNP rs6587666 was negatively associated with eczema in additive model ( OR : 0.66, 95% CI: 0.47–0.93, P : 0.017). Moreover, African ancestry modifies the association between rs6587666 and eczema. The effect of the T allele was higher among individuals with higher African ancestry and the association with eczema was lost in individuals with lower African ancestry. In our analyses the expression of FLG in skin was slightly downregulated by the presence of the T allele of rs6587666. In our population, the T allele of rs6587666 in FLG was associated with protection to eczema and the degree of African ancestry was able to modify the observed association. Highlights: The T allele of the rs6587666 SNP was negatively associated with eczema. AsSociation between rs6587666 and eczema changed according to the African ancestry. The higher is the negative association with eczema, higher is the African Ancestry. In individuals with a lower African Ancestry, no association with eczema was found.